Soil not fire: Field, glasshouse and dendrochronology studies show how edaphic factors control post-fire woody plant growth across a sedgeland – forest boundary in Tasmania - Prior, Lynda D.; Nichols, Scott C.; Foyster, Scott M.; Ondei, Stefania; Bowman, David M.J.S. (Forest ecology and management, 2024)
Western Tasmania contains large areas of treeless sedgeland interspersed with scrub and forest vegetation. Why these large treeless areas exist in a region wet enough to support rainforest remains unclear. Slower growth of woody plants in the sedgeland than the scrub and forest could be a factor, because smaller woody plants are more likely to be killed by frequent fire before they mature and set seed. However, there is little information regarding growth rates of woody plants in these communities. We characterised soils and compared growth rates of small woody plants in sedgeland, scrub and forest at two sites using diverse approaches: (i) field observational studies of seedlings from a broad range of species that established following a wildfire in 2019 at site 1; (ii) a dendrochronological study of mature myrtaceous shrubs that had established following a fire in 1983 and were killed by the 2019 fire at site 1 (iii) a field experiment in which fertiliser was applied to transplanted seedlings of the myrtaceous shrub Leptospermum scoparium at site 2. (iv) We also used a glasshouse experiment to test the effects of nutrients and waterlogging on L. scoparium seedlings. Sedgeland soils were organic and poorly drained, whereas forest soils were mineral and well drained; scrub soils were organic at the surface but well drained. Concentrations of most soil nutrients, including total P, K, Ca, Mg and Mn were highest in the forest, although N was highest in sedgeland. At both sites, woody plant species grew faster in scrub and forest than in sedgeland, by a factor of 1.7–3.4. When fertiliser was added to transplanted L. scoparium seedlings, there was no difference in growth between sedgeland and scrub. In the glasshouse experiment, growth was limited by both low soil nutrients and waterlogging. However, the waterlogging effect was not apparent in the field experiment because conditions were dry. Our study shows slow growth of woody plants in Tasmanian sedgelands associated with infertile and waterlogged organic soils. Fire disturbance sharpens the boundary but is not the cause of it. •Tasmania contains areas of treeless sedgeland interspersed with forest and scrub.•An unproven hypothesis is that tree growth is slower in sedgeland.•We conducted observational and experimental growth studies in field and glasshouse.•All studies showed slower tree growth in sedgeland than scrub or forest.•Edaphic factors (low nutrients and waterlogging) can explain slower tree growth.